Fire and Ice: Contrasting Different Personalities in the movie “Rush” (2013) by Ron Howard - Wicaksana, Rayhan Racha; Apriliani, Salwa Nur; Faisal, Faisal (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This research explores the contrasting personalities of James Hunt and Niki Lauda as portrayed in Ron Howard’s Rush, examining their impact on the film’s narrative and its appeal to a global audience. Employing a qualitative approach, the study focuses on key character traits and dialogue to identify six examples of their differing personalities. Hunt is depicted as passionate and impulsive, embracing the joys of the present, while Lauda is methodical and disciplined, prioritizing control and long-term success. These opposing traits not only shaped their iconic rivalry but also defined their approaches to life and competition. The research involved multiple viewings of the film to analyse how these traits were presented and their significance within the story. By comparing and contrasting these characters, the study highlights the interplay between passion and precision, demonstrating how their differences drove both conflict and mutual respect, contributing to one of Formula 1’s most legendary rivalries.